Democratization and budget openness: evidence from Hong Kong, Macao and Taiwan. (June 2021) - Fong, Brian C.H.
The existing literature postulates that budget openness often improves at critical moments of democratization. Hong Kong, Macao and Taiwan, which are transitional regimes currently experiencing different regime trajectories, should be ideal places to test the validity of this theory. By examining whether and how open budget reforms in Hong Kong, Macao and Taiwan are related to their regime trajectories through historical-comparative case studies, this article aims to make an original contribution to the comparative budgeting literature by providing a new and unique set of Open Budget Survey-based case studies in the context of East Asian transitional regimes. Points for practitioners: This article uses comparative studies of Hong Kong, Macao and Taiwan to illustrate the politics of budget openness facing policymakers in the process of democratization. For policymakers, the lesson from the comparative studies is that the rise of competitive electoral and legislative politics will bring about pressures for open budget reforms. More policy learning is necessary for policymakers from different types of political regimes to share the experiences of handling the politics of budget openness.